Adaptive Reasoning Based on Microsoft Mathematics - Susilawati, Wati; Rachmawati, Tika Karlina; Nuraida, Ida (JTAM (Jurnal Teori dan Aplikasi Matematika), 2021)
The demands of professional teachers to design technology-assisted learning that can facilitate all students to develop their potential. the fact that the quality of students' adaptive reasoning in solving math problems is still low which has an impact on other mathematical competencies. The purpose of this study was to determine the differences in the improvement of adaptive reasoning abilities between students who have implemented Search Solving Create and Share learning assisted with Microsoft Mathematics and conventional learning. The method used is quasi-experimental with the non-equivalent pre-test and post-test control group design. Through the Simple Random Sampling technique, two classes were selected, namely class X1 and X2 one of the SMA in Bandung Indonesia. Test instrument: story questions about adaptive reasoning abilities. Analysis using independent T-test data. Result: There is a difference in the improvement in adaptive reasoning abilities between students who using search-solve-create- share learning assisted by Microsoft mathematics compared to conventional learning. Students' difficulties in solving story problems with adaptive reasoning abilities can be minimized by getting used to solving non-routine story problems. Learning search-solve-create-share assisted by Microsoft mathematics accustoms students to convey assumptions, provide reasons for answers, draw conclusions from statements, and students can find patterns of various mathematical problems through multi-interactive media.